(untitled) (African Journal of Biomedical Research, 2023)
Long-distance truck drivers (LDTDs) have a higher rate of HIV infection than the general population. This is attributed to their high mobility and their being out of their homes for protracted periods. LDTDs stop for a day or more at Kazungula weigh bridge terminal, making it a lucrative rendezvous for commercial sex work. Risky sexual behaviour predisposes LDTDs to contracting and spreading HIV. The aim of this study is to determine the level of knowledge of HIV/AIDS and the sexual behaviour of the LDTDs at Kazungula weigh bridge terminal. Quantitative, cross-sectional-descriptive methods were employed to study the LDTDs at Kazungula weigh bridge terminal in the Chobe District. A simple random sampling technique was used to produce a sample of 399 truck drivers who consented to participate in the study. A questionnaire (written in English and translated into Setswana) was used to collect socio- demographic data and establish the knowledge of HIV/AIDS and sexual behaviours of LDTDs. A total of 399 LDTDs participated in this study. The level of knowledge about HIV/AIDS was high among the LDTDs, but regardless of this, LDTDs engaged in sexually risky behaviours. All participants (100%) had heard about HIV/AIDS and the common sources of information were the media (65.9%) and school (62.9%). Most of the LDTDs (96.99%) knew that AIDS is caused by HIV, and the level of education was not a predictor of the level of knowledge of HIV/AIDS among the LDTDs, with a correlation of 0.597 (not significant). About 12.03% believed that HIV/AIDS is caused by witchcraft and 23.31% did not agree that HIV/AIDS has no cure. This has an association with the level of education (P<0.05. The results revealed that 90.23% of participants agreed that HIV can be prevented by using a condom (P<0.021). Despite the high level of knowledge about HIV/AIDS found in this study, LDTDs still engaged in sexually risky behaviours such as paying to have sex with commercial sex workers-CSW (56.89%) and having sex with commercial sex workers without using a condom (27.07%). The study shows that LDTDs engage in sexually risky behaviours despite having a high level of knowledge about HIV/AIDS. To abate the problem of new infections and re-infections with HIV in this group and in the general population, effort needs to be geared towards LDTDs behaviour change. It is envisaged that such behavioural change would promote the use of condoms particularly with CSWs and casual partners